Compounds purified from edible fungi fight against chronic inflammation through oxidative stress regulation - Xia, Yidan; Wang, Dongxu; Li, Jiaqi; Chen, Minqi; Wang, Duo; Jiang, Ziping; Liu, Bin (Frontiers in Pharmacology, 2022)
Chronic inflammation is associated with various chronic diseases, including cardiovascular disease, neurodegenerative disease, and cancer, which severely affect the health and quality of life of people. Oxidative stress induced by unbalanced production and elimination of reactive oxygen species (ROS) is one of the essential risk factors for chronic inflammation. Recent studies, including the studies of mushrooms, which have received considerable attention, report that the antioxidant effects of natural compounds have more advantages than synthetic antioxidants. Mushrooms have been consumed by humans as precious nourishment for 3,000 years, and so far, more than 350 types have been identified in China. Mushrooms are rich in polysaccharides, peptides, polyphenols, alkaloids, and terpenoids and are associated with several healthy biological functions, especially antioxidant properties. As such, the extracts purified from mushrooms could activate the expression of antioxidant enzymes through the Keap1/Nrf2/ARE pathway to neutralize excessive ROS and inhibit ROS-induced chronic inflammation through the NF-κB pathway. Recently, the antioxidant properties of mushrooms have been successfully applied to treating cardiovascular disease (CAD), neurodegenerative diseases, diabetes mellitus, and cancer. The present review summarizes the antioxidant properties and the mechanism of compounds purified from mushrooms, emphasizing the oxidative stress regulation of mushrooms to fight against chronic inflammation.